1996
DOI: 10.1364/ao.35.002537
|View full text |Cite
|
Sign up to set email alerts
|

Iterative inversion of phase-Doppler-anemometry size distributions from sprays of optically inhomogeneous liquids

Abstract: Using phase Doppler anemometry (PDA) to investigate sprays of optically inhomogeneous liquids leads to blurred measured size distributions. The blurring function is formed by performance of PDA measurements on single-size droplets generated by a piezoelectric droplet generator. To obtain the undistorted droplet-size distributions, a constrained iterative inversion algorithm is applied. The number of iteration steps to achieve the best possible restoration is determined by the use of synthetically generated dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Therefore, special algorithms have to be applied to compute the unknown diameter distribution q(d). The transfer function has to be known; it can be found by measuring a larger number of monodispersed droplets [11].…”
Section: Mathematical Inversion Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, special algorithms have to be applied to compute the unknown diameter distribution q(d). The transfer function has to be known; it can be found by measuring a larger number of monodispersed droplets [11].…”
Section: Mathematical Inversion Algorithmmentioning
confidence: 99%
“…Thus, with the found 'real distribution', simulations were performed to optimize the number of iteration steps. Details about this optimization process can be found in [11]. For our application this optimization was further improved by distributing the random numbers according to the supposed diameter distribution.…”
Section: Mathematical Inversion Algorithmmentioning
confidence: 99%
“…Domnick et al (1994) measured a paint spray with metal flakes in the droplets and found that PDA retains reasonably good linearity between the measured phase and the diameter even with flakes in droplets, although this is apparently not consistent with the experimental results of Wriedt et al (1993). The work done by Wriedt et al has been complemented by introducing a scheme for correction of the size distribution, based on deconvolution (Wriedt et al 1993, Köser andWriedt 1996) which worked well with certain presumed size distribution functions. In addition, Schneider and Hirleman (1994) investigated PDA sizing for particles with symmetrical refractive index gradients within the spherical particles and Onofri et al (1996) have also evaluated the response of PDA to multi-layered droplets.…”
Section: Introductionmentioning
confidence: 98%
“…Dual-mode PDA permits measurements under such severe conditions, but at the possible expense of a reduced acceptance rate. Another approach is based on a mathematical correction of measured polydisperse size distributions by a deconvolution technique [4]. This method was later verified experimentally [5] by investigating suspension droplets.…”
Section: Introductionmentioning
confidence: 99%